Penambahan Prosedur dan Syarat Pesawat Melakukan Circling Approach Menuju Runway 35 Pada SOP Bandar Udara Internasional Sultan Iskandar Muda - Muhammad Caesar Akbar; Rafif Pradya Mulyana (Politeknik Penerbangan Makassar, 2023)
The use of the Circling Approach is to increase awareness and familiarity with the controller so that it can reduce risk, increase safety and make it easier for the controller to accelerate and maintain the regular flow of air traffic. So there needs to be an effort and real steps to improve quality, professionalism, productivity, and work ethic. high level of existing human resources. The research objective in this on the job training report is the pattern circling approach runway 17 to 35 in order to create maximum service for air transportation service users both in terms of safety and efficiency. the method used by the author in this study is a kualitatif method and descriptive method. Researchers describe events and events at the Sultan Iskandar Muda international airport with a circling approach using runway 35. Based on the research that the author has carried out, making a pattern circling approach on runway 17 to runway 35 has a predetermined altitude and speed procedure as a requirement based on the rules in DOC 8168 PANS-OPS is one of the best ways to solve this problem, so that if there are aircraft those experiencing factors that cause a missed approach do not need to re-approach on runway 17, the controller can immediately advise the pilot to do a circling approach so that the aircraft movement becomes more efficient and lands on runway 35.